Representasi Iman dan Budaya dalam Jalan Salib dan Jumat Agung di GKPA Sibadoar - Sinaga, Ester; Fadlin, Fadlin; Gulo, Hubari (Jurnal Pendidikan dan Penciptaan Seni, 2025)
This study examines the representation of faith and culture in the celebration of the Stations of the Cross and Good Friday at GKPA Sibadoar, Sipirok District, South Tapanuli Regency. Good Friday is an important day for Christians to commemorate the crucifixion and death of Jesus Christ. This research aims to describe the manifestation of faith and culture in the Good Friday worship and the Stations of the Cross performance at GKPA Sibadoar. The study uses a qualitative approach with Koentjaraningrat’s Religious Ceremony Theory to analyze the worship, and Milton Singer’s Theory to describe the cultural performance. Data collection techniques were carried out through observation, interviews, and audio-video documentation. The results show that the Good Friday service at GKPA Sibadoar is conducted solemnly and simply, emphasizing Scripture readings, prayers, and reflections on Christ’s suffering, thus strengthening the congregation’s solidarity. The theatrical performance of the Stations of the Cross involving church youth serves as a medium for transmitting faith and expressing local culture. Furthermore, the hymns sung during worship feature strophic melodic patterns, predominantly stepwise intervals, and hanging contours that support the contemplative atmosphere. This study reveals a harmonious integration between religious and cultural values in the celebration of the Stations of the Cross and Good Friday at GKPA Sibadoar, which strengthens the congregation’s faith while preserving local culture